MERAJUT BUDAYA DAN PERDAGANGAN PECINAN GLODOK MELALUI PENDEKATAN PLACEMAKING - Therik, Andrea Georgina; Santoso, J.M. Joko Priyono (Jurusan Arsitektur dan Perencanaan, 2024)
Pecinan Glodok is the largest area in Jakarta with a rich Chinese cultural heritage, predominantly inhabited by ethnic Chinese descendants. Currently, the identity of Pecinan Glodok has faded over time. In the past, Glodok was known as a center of commerce and socio-cultural activities. However, today, Glodok's trade survives in a shabby and disorganized state, overshadowing the cultural activities that could thrive. This study aims to restore Pecinan Glodok's identity through a placemaking approach and traditional Chinese architectural concepts, particularly the principles of symmetry and balance. The study identifies factors contributing to the